WATER POLITICS IN BRAZIL: SUBSIDIARITY AND HUMANITY ASPECTS FOR THE SEMI ARID SUSTAINABLE RIVER BASIN MANAGEMENT - Borba Vilar Guimarães, Patricia; Marcius de Alencar Xavier, Yanko (Revista Direito E-nergia, 2013)
WATER POLITICS IN BRAZIL: SUBSIDIARITY ANDHUMANITY ASPECTS FOR THE SEMI ARID SUSTAINABLERIVER BASIN MANAGEMENT